(untitled) (The Research of Medical Science Review, 2023)
Epigenetics, the study of heritable changes in gene expression without altering the DNA sequence, has emerged as a powerful force in understanding disease development and progression. This comprehensive review delves into the intricate interplay between epigenetic mechanisms, such as DNA methylation, histone modifications, and non-coding RNAs, and their contribution to various diseases. The review explores how epigenetic alterations can influence gene expression patterns, leading to disruptions in cellular processes and contributing to the onset and severity of diverse conditions. It examines the role of epigenetics in diseases ranging from cancer and autoimmune disorders to neurological and psychiatric conditions. Furthermore, the review discusses the potential of epigenetic markers as biomarkers for disease diagnosis, prognosis, and personalized medicine strategies. It highlights the promise of targeting epigenetic mechanisms for therapeutic interventions, offering novel approaches beyond traditional treatments. Keywords: Epigenetics, DNA methylation, histone modifications, non-coding RNAs, diseases, gene expression, pathogenesis, therapeutics.